Necessary and sufficient condiitions for multiobjective optimization problems - Taa, A. (Optimization, 1996)
We consider the following multiobjective optimization problem (P) Minimize F(x) subject to x ∈ X where Fis a set-valued map between two Banach X and Y. When the set-valued map F is upper somedifferentiable and compact Luc [2] gives necessary and sufficient optimality conditions for (P) in terms of contingent derivatives. In this paper we study the same problem under weaker notion of set-valued derivatives and without nether compactness nor upper somedifferentiability assumptions